Construction management fundamentals - Schexnayder, Cliff J. (McGraw-Hill Higher Education, 2004)
This first edition of Construction Management Fundamentals is general in terms of individual construction process activities and comprehensive in terms of construction fundamentals (get work, do work, keep score). This is a comprehensive new text for the emerging Construction Fundamentals course taught to non-construction engineering and architecture majors taking only one or two construction courses. These students are not majoring in construction and have very little knowledge of the construction industry, construction processes, or how projects are executed.